PENGGUNAAN LINGUISTIK KORPUS DALAM MEMPERSIAPKAN BAHAN AJAR ENGLISH FOR SPECIFIC PURPOSE Di BIDANG RADIOLOGI: The Use of Corpus Linguistics in Preparing Teaching Materials of English for Specific Purposes in the Field of Radiology - Euis Reliyanti Arum; Wiwin Winarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2020)
The limited sources of English for Specific Purpose textbooks relating to Radiology that is suitable for radiology study program students in Indonesia become a challenge for English language lecturers at Politeknik Al Islam of Bandung. To anticipate the limited ESP teaching materials, researchers conducted a study on an English radiology textbook by using a linguistic corpus as a tool for obtaining radiological vocabularies as well as grammar and word classes features used in the textbook. This study used a mix method combining quantitative method applied at the beginning of the study and qualitative method used in the analysis process to draw conclusions. The results showed that there were 12,395 different words used in the textbook with a total number of words including repeated words as many as 428,117 words. These words were classified into noun, verb, adjective, and adverb classes as well as abbreviations and others. Generally, results of the analysis showed the use of active and passive sentences, tenses including simple present, present continuous, past, present perfect, auxiliary verbs, countable and uncountable nouns, and comparative degree. Furthermore, the results will be used to arrange ESP teaching materials in the field of radiology.